Hemispheric asymmetry of the dayside aurora due to imbalanced solar insolation - Kan Liou (Nature Portfolio, 2020)
Abstract Unlike the nightside aurora, which is controlled mainly by magnetic field reconnection in the magnetotail, the dayside aurora is closely associated with magnetic field merging at the dayside magnetopause. About two decades ago, it was discovered that the aurora is also controlled by solar insolation. Because the finding was based on data acquired mainly in the Northern Hemisphere, an outstanding question is if the auroral solar insolation effect also exists in the Southern Hemisphere. The present study addresses this question by studying dayside auroras from both hemispheres. We analyze 6 years’ worth of Earth disk emissions at far ultraviolet wavelengths acquired by the Global UltraViolet Imager on-board the Thermosphere Ionosphere Mesosphere Energetics and Dynamics satellite from 2002 to 2007. It is found that the solar insolation effect also exists in the Southern Hemisphere. In essence, the energy flux deposited as electron precipitation, is larger when the polar hemisphere is sunlit and is smaller when the polar hemisphere is dark. Because auroras are produced mainly by electron precipitation and because electrons are the main current carrier, this north–south asymmetry is consistent with the previous finding that larger (smaller) field-aligned currents are flowing out of the sunlit (dark) hemisphere. This trend is independent of the solar wind driving, suggesting that it is an effect associated with solar insolation. A small north–south asymmetry in the dayside auroral energy flux was identified. We discuss the asymmetry in the context of magnetospheric current and voltage generators.